ANALYSIS OF STUDENT ERRORS IN SOLVING SPLDV QUESTIONS BASED ON CASTOLAN STAGES REVIEWED FROM STUDENTS' COGNITIVE STYLE - Evinia Kusuma Dewi; Nizaruddin Nizaruddin; Agnita Siska Pramasdyahsari (International Journal of Research in Education, 2021)
This study aims to determine the description of students' errors in solving SPLDV questions in terms of students' reflective and impulsive cognitive styles. This research is a qualitative research using a descriptive approach which was carried out at MTs Husnul Khatimah 02 Semarang in the 2020/2021 academic year. The subjects of this study were grade VIII students with reflective and impulsive cognitive styles. The instrument used is a cognitive style questionnaire, namely the Matching Familiar Figure Test (MFFT) developed by Warli, the SPLDV problem solving test and interview guidelines. Checking the validity of the data in this study is time triangulation. The indicator of student errors is based on the Kastolan stages, namely procedural errors, conceptual errors, and technical errors. The results of this study are students with an impulsive cognitive style tend to have more errors than students with a reflective cognitive style. Internal factors that cause errors are because students are less thorough, lack of practice questions, do not understand the prerequisite material, do not understand the concept of solving linear inequality problems of two variables, and do not understand the basic concepts of elimination and substitution methods, while the external factor is the lack of time given to students. so that students have not finished working on the questions